Answer:
f(3) = 3
Step-by-step explanation:
f(1) = 1
f(2) = 2
f(n) = f(n − 2) + f(n − 1)
f(3) = f(3 - 2) + f(3 - 1)
= f(1) + f(2) = 1 + 2 = 3
Special Note: Have you heard of the Fibonacci sequence?
The formula f(n) = f(n − 2) + f(n − 1) is used to find the terms of the of the Fibonacci sequence
Answer: $7.00
Step-by-step explanation:
each foot is $1, so times 7 is 7 dollars.
Answer:
me niether
Step-by-step explanation:
lol
Answer:
Answer
1
Answer:
they ate the some area just one is
stretched out more than the other one
Just draw a line from point D join to point
E
The triangle formed DME will be
congruent to AMC
Explanation: